Recent Antibiotic Sensitivity Pattern of Escherichia Coli in Urinary Tract Infection - Bari, Md Abdul; Arefin, Mashiur; Nessa, Moriom; Mostofa, Golam; Islam, Tafiqul (TAJ: Journal of Teachers Association, 2018)
The objective of the study is to assess the recent sensitivity pattern of Escherichia coli in Urinary tract infection (UTI). Widespread use of antibiotics has led to the emergence of resistant microorganisms. As the antibiotic sensitivity patterns of the microorganisms are frequently changing, this retrospective analysis was designed to assess the recent antibiotic sensitivity pattern of Escherichia coli (E. coli) in urinary tract infection among the human population. Details of 358 urine culture positive reports for E. coli and their antibiotic sensitivity pattern pertaining to the study period of 6 months from Jan 2017 to June 2017 were collected from Microbiology Laboratory of Diagnostic Centers at Rajshahi and the results were statistically analyzed. The antibiotics tested for sensitivity were amikacin, gentamycin, ciprofloxacin, levofloxacin, cotrimoxazole, nitrofurantoin, ceftazidime, ceftriaxone and cefixime. The sensitivity pattern of E.coli to antibiotics in UTI was amikacin (82.68 gentamycin (75.97%), nitrofurantoin (70.67), levofloxacin (44.13%), ceftazidime (42.17%), co-trimoxazole (40.78%), ceftriaxone (38.54%), ciprofloxacin (35.75%), and cefixime (24.02%). The study highlighted the marked resistance of E. coli to quinolones and third generation cephalosporins. TAJ 2017; 30(1): 61-65